The Role of Green Ecology in Mitigating Climate Risks to Banjarbaru's Rice - Najwa, Nugraha Anthoni; Rizali, Akhmad; Abbas, Saipul (Jurnal Biologi Tropis, 2024)
Climate change poses a significant threat to agricultural productivity, particularly in regions like Banjarbaru, Indonesia. This study investigates the impact of climate change on rice farming in Banjarbaru and explores the potential of green ecology practices to mitigate these effects.The research employed a mixed-methods approach, combining quantitative and qualitative data collection techniques. Findings reveal that fluctuating weather patterns, including prolonged droughts and floods, have severely impacted rice cultivation. Farmers reported decreased yields, disrupted planting schedules, and increased pest and disease outbreaks.To address these challenges, the study highlights the importance of adopting green ecology practices, such as organic fertilizer use, integrated pest management, and the utilization of local wisdom-based techniques. These practices can improve soil health, reduce reliance on chemical inputs, and enhance overall agricultural sustainability. However, limited awareness and insufficient government support remain major obstacles to their widespread adoption.Recommendations include improved water governance, increased support for sustainable agriculture, facilitated market access for green products, and enhanced government engagement to foster a climate-resilient agricultural system in Banjarbaru. By implementing these measures, Banjarbaru can mitigate the adverse impacts of climate change and ensure long-term food security.